A Transparent Logic Circuit for RFID Tag in a‐IGZO TFT Technology. Issue 4 (30th August 2013) - Yang, Byung‐Do; Oh, Jae‐Mun; Kang, Hyeong‐Ju; Park, Sang‐Hee; Hwang, Chi‐Sun; Ryu, Min Ki; Pi, Jae‐Eun
Abstract : This paper proposes a transparent logic circuit for radio frequency identification (RFID) tags in amorphous indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT) technology. The RFID logic circuit generates 16‐bit code programmed in read‐only memory. All circuits are implemented in a pseudo‐CMOS logic style using transparent a‐IGZO TFTs. The transmittance degradation due to the transparent RFID logic chip is 2.5% to 8% in a 300‐nm to 800‐nm wavelength. The RFID logic chip generates Manchester‐encoded 16‐bit data with a 3.2‐kHz clock frequency and consumes 170 μW at V DD = 6   V . It employs 222 transistors and occupies a chip area of 5.85 mm 2 .